Feasibility and kinetics of CD34+ hematopoietic progenitor cell mobilization in response to a single administration of docetaxel chemotherapy and pegfilgrastim in a contemporary cohort of patients with metastatic breast cancer. Issue 1 (21st September 2016) - Takhar, Harminder; Mislang, Anna Rachelle; Singhal, Nimit; Brown, Michael P
Abstract: Aim: Autologous hematopoietic stem cell transplantation (auto‐HSCT) remains an experimental therapy for metastatic breast cancer (MBC) and there is no established protocol for cluster of differentiation 34 + (CD34 + ) hematopoietic progenitor cell (HPC) mobilization with historic studies using growth factors with or without chemotherapy. This study describes the feasibility and kinetics of CD34 + HPC mobilization following a single administration of docetaxel and the pegylated form of recombinant human granulocyte colony‐stimulating factor analogue filgrastim (pegfilgrastim). Methods: The study design was serial measurement of peripheral blood CD34 + HPC in patients with MBC following a single administration of intravenous (IV) docetaxel 100 mg/m 2 on day 1 and subcutaneous (SC) pegfilgrastim 6 mg on day 2. Results: Eight patients with MBC were enrolled. The median age was 56 years (range 51–75 years). All patients had human epidermal growth factor receptor 2 (HER2) negative disease and either hormone refractory or negative disease. Three patients had bone only disease, four had visceral organ disease with or without bone involvement and one had locally unresectable disease only. All patients had prior therapy for early‐advanced stage disease and prior therapy for MBC included seven patients receiving at least one line of hormone therapy and three having palliative chemotherapy. Six patients recorded a rise in the CD34 + count greater than 20 cells/μL. The median peak level was 40.2 cells/μL (standard deviation = 28.7) occurring on day 9 and with an average duration of 4 days. Overall, treatment was well tolerated with manageable side‐effects. Conclusion: The single administration of docetaxel and pegfilgrastim was effective in mobilization of CD34 + HPC and peak levels followed a predictable course. This approach needs validation in prospective studies by preparation of auto‐HSCT by leukapheresis and quantification of total CD34 + HPC yields.